Acute air pollution exposure and gastrointestinal cancer mortality: a case-crossover study in coastal China - Wu, Zhuchao; Wei, Chaohua; Sun, Jian; Qiu, Beibei; Kong, Weimin; Yang, Yang; Huang, Yanqiu; Li, Cheng; Wu, Lingling; Liu, Fudong; Wang, Xiaojie (Frontiers in Public Health, 2025)
BackgroundGastrointestinal (GI) cancers account for 43.1% of cancer-related deaths in China, with aging populations exacerbating this burden. While chronic air pollution exposure is linked to GI carcinogenesis, evidence on acute effects remains limited. This study investigates short-term ambient pollutant exposure and GI cancer mortality in a coastal Chinese city with moderate pollution levels.MethodsUsing death registry data from Yancheng, China (2013–2022; n = 104,216 GI cancer deaths), we employed a time-stratified case-crossover design combined with distributed lag nonlinear models (DLNM) to assess associations between daily PM2.5, PM10, SO2, NO2, and O3 concentrations (lag 0–7 days) and mortality. Stratified analyses by age, sex, and cancer subsite were conducted, with sensitivity analyses evaluating model robustness.ResultsA 10 μg/m3 increase in PM2.5, PM10, and O3 was associated with acute GI cancer mortality, peaking at lag 0–5 days (relative risk [RR] = 1.011, 95% CI: 1.000–1.022 for PM2.5; RR = 1.009, 95% CI: 1.001–1.017 for PM10; RR = 1.008, 95% CI: 1.001–1.016 for O3). The older males (≥65 years) exhibited heightened vulnerability, with maximal cumulative RRs of 1.018 (PM2.5), 1.010 (PM10), and 1.014 (O3). Esophageal cancer showed acute PM sensitivity (lag 0–4 days: RR = 1.021 for PM2.5), while colorectal cancer mortality correlated with delayed O3 effects (lag 0–7 days: RR = 1.031). No associations were observed for SO2 or NO2. Sensitivity analyses confirmed model stability across pollutant co-exposure adjustments and temporal confounders.ConclusionShort-term exposure to PM2.5, PM10, and O3 elevates GI cancer mortality risk, particularly among the older males and upper GI malignancies. These findings highlight the need for revised air quality standards addressing acute exposure thresholds and targeted protections for high-risk populations to mitigate pollution-related cancer mortality.